Analysis of sports supplement consumption in 1688 federated road cyclists - García-Durán, J.; González-Jurado, J. A.; Sánchez-Oliver, A. J. (Nutrients, 2024)
The widespread use of sports supplements (SS) to enhance athletic performance extends to cyclists, although little research has been conducted on this subject within this sport. This descriptive and cross-sectional study involved 1688 federated road cyclists, aiming to analyse the pattern of SS consumption concerning the degree of scientific evidence and different categories. This study categorised SS based on the groups and subgroups established by the Australian Sport Institute (AIS, 2023) based on the level of evidence. Our results showed that 62.5% of the sample cyclists used SS, with an average of 12.2 ± 8.6 supplements consumed per participant. Health status (78.2%), pharmacies (62.5%), and medical doctors (45.7%) were the main reasons, purchase sites, and sources of information for SS consumption, respectively. The most prevalent SS consumed were Sports Gels (94%), Sports Bars (89.3%), and Sports Drinks (73.8%). Notably, 80% of the top ten most consumed SS belonged to the group with the highest level of evidence according to the AIS, with an average of 6.9 ± 3.2 supplements per participant. However, 23.3% of the total SS consumers used prohibited substances. In conclusion, while the prevalence of SS consumption among road cyclists is considerable and the primary sources for purchasing SS and obtaining advice are reliable, there is a notable prevalence of prohibited substance use within the sample.